Accretion of volatile elements on Earth without the need of a late veneer - Lucas Calvo; Siebert, Julien; Huang, Dongyang; Ingrid Blanchard; Kubik, Edith; Valentina Bonino; Anja Schreiber; Avice, Guillaume; Jabrane Labidi (Science Advances, 2026)
Volatile elements are essential for life development and planetary evolution. However, the timing of their delivery to terrestrial planets remains unclear. Sulfur, selenium, and tellurium are volatiles, but also siderophile elements. Their abundances in Earth’s mantle can be used to determine whether volatile elements were delivered to Earth during or after the segregation of the core. Here, we experimentally measured their partition coefficients between core-forming metal and mantle silicate under pressure, temperature, and oxygen fugacity conditions relevant to a deep magma ocean. Our results show that these elements exhibit similar partitioning behaviors, indicating that core-mantle equilibrium preserves their chondritic relative abundances. If a volatile-rich late veneer has been delivered to Earth after core segregation, it must have been limited in mass, making up a maximum of 0.1% Earth’s mass. This suggests that volatile elements, including water, were accreted continuously during Earth’s growth rather than being delivered predominantly by a late veneer of volatile-rich material such as carbonaceous chondrites.